Calcareous Algae (Lithothamnium calcareum) as an Alternative Source of Calcium in Commercial Layer Diets - Ávila, L. R.; Cruz, F. K.; Leite, B. K. V.; Garcia, E. R. M. (Tropical Animal Science Journal, 2025)
Calcareous algae (CA) are an alternative renewable source of organic minerals that are used in poultry feed. However, the optimal CA concentration that can be included in poultry diets and its effect on egg production requires further investigation. The aim of this study was to determine the effects of diets containing varying CA (Lithothamnium calcareum) levels and particle sizes on the performance, mineral balance, quality, and composition of the eggs of commercial laying hens. A completely randomized experimental design with a 3 × 2 factorial arrangement (CA level × particle size) was employed in this study. A total of 210 Dekalb White laying hens were distributed to the following experimental units, with six birds each and five replicates per unit: the control (diet without CA addition) and treatment groups, which were fed with diets containing varying CA levels (1%, 2%, and 3%) and particle sizes (0.128 and 1.114 mm). Productive performance, external egg quality, and percentage of non-viable eggs were not affected by the inclusion of CA in the diets. The inclusion of 2% fine-particle CA reduced (p